Training and Profile of Special Olympics Portugal Coaches: Influence of Formal and Non-Formal Learning - Pires, Pedro Rui (2021)
Since coaches play an important role in the development of athletes, the process and mechanisms used by Special Olympics Portugal to develop coaches’ skills are worthy of research. In this context, the study aims to identify the training paths and profiles of the Special Olympics Portugal coach. It also aims to analyze the relationship between formal and non-formal learning in the profile and training of this type of coach. The research is descriptive and transversal regarding Special Olympics Portugal coaches, with the participation of 50 subjects. Two questionnaires were used, the Coaches’ Training Profile Questionnaire to determine the training routes, and the Coaches’ Orientation Questionnaire. The results show that the Special Olympics Portugal coaches have an academic background and a somewhat critical profile. It is imperative to build formal and non-formal learning contexts that focus on the theme of adapted sports, in order to allow the training of more qualified coaches, who are consequently more effective in their interventions with this type of athlete.